Linearly Tunable Emission Colors Obtained from a Fluorescent–Phosphorescent Dual‐Emission Compound by Mechanical Stimuli1. (7th April 2015) - Mao, Zhu; Yang, Zhiyong; Mu, Yingxiao; Zhang, Yi; Wang, Yi‐Fan; Chi, Zhenguo; Lo, Chang‐Cheng; Liu, Siwei; Lien, Alan; Xu, Jiarui
Abstract Organic mechanoluminochromic materials are mechano/piezo‐responsive and promising for applications in sensors, displays, and data storage devices. However, their switching range of emission is seriously impeded by only one kind of emission (either a fluorescent or phosphorescent peak) in the spectrum of single organic compounds. This study presents a design strategy for pure organic compounds with excellent room‐temperature fluorescent–phosphorescent dual‐emission (rFPDE) properties, which combines the effective factors of dipenylsulfone group, crystalline state, and heavy atom effect. Following the principle of color mixing, myriad emission colors with a wide range from orange to purple and across white zone in a straight line in the chromaticity diagram of the Commission Internationale de l'Eclairage (CIE) can be obtained by simply mechanical grinding the compound. The unique properties could be concentrated on a pure organic compound through this design strategy, which provides a new efficient channel for the discovery of efficient mechano‐responsive organic materials.